2018
DOI: 10.1002/chem.201802764
|View full text |Cite
|
Sign up to set email alerts
|

Ensemble versus Local Restructuring of Core‐shell Nickel–Cobalt Nanoparticles upon Oxidation and Reduction Cycles

Abstract: Bimetallic nanoparticles are widely studied, for example in catalysis. However, possible restructuring in the environment of use, such as segregation or alloying, may occur. Taken individually, state-of-the-art analytical tools fail to give an overall picture of these transformations. This study combines an ensemble analysis (near-ambient-pressure X-ray photoelectron spectroscopy) with a local analysis (environmental transmission electron microscopy) to provide an in situ description of the restructuring of co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“…[35] The oxidized species observed for Ni (light green), Co (light red) and P (light blue), were expected as they were possibly formed during the synthesis and/or as the result of the washing in air. However the presence of these species was not an issue for the catalytic reaction: since it was conducted in reducing conditions, it is expected that the surface state presents less oxidized species, as evidenced previously by near-ambient pressure XPS on NiCo NPs [33] and in agreement with our recent work. [28] Moreover, the presence of reduced P species of phosphide type suggested that some P was incorporated in the metallic surface, a phenomenon previously observed on NiCo nanoparticles.…”
Section: Chemcatchemsupporting
confidence: 90%
See 1 more Smart Citation
“…[35] The oxidized species observed for Ni (light green), Co (light red) and P (light blue), were expected as they were possibly formed during the synthesis and/or as the result of the washing in air. However the presence of these species was not an issue for the catalytic reaction: since it was conducted in reducing conditions, it is expected that the surface state presents less oxidized species, as evidenced previously by near-ambient pressure XPS on NiCo NPs [33] and in agreement with our recent work. [28] Moreover, the presence of reduced P species of phosphide type suggested that some P was incorporated in the metallic surface, a phenomenon previously observed on NiCo nanoparticles.…”
Section: Chemcatchemsupporting
confidence: 90%
“…It confirmed the formation of an oxidized layer on the surface of the nanoparticles. The spectra were analyzed with CasaXPS following the methodology of our previous works [30,[32][33][34][35] and fitting parameters can be found in the SI. The Ni 2p region (Figure 2C) was fitted with two components: [36] metallic nickel at a binding energy (B.E.)…”
Section: Chemcatchemmentioning
confidence: 99%
“…Thus, it can better encapsulate and protect the nanoparticles. [25] Additionally, TEM of SA/NÀ Co x O y was also detected, and the results are displayed in Figure 2(e) and Figure 2(f). Obviously, all the nanoparticles were quite uniformly dispersed in hydrogel beads interior without aggregation and agglomeration, which is in consistent with the outcomes of SEM.…”
Section: Sem and Tem Resultsmentioning
confidence: 89%
“…Some hexagonal expanded pores and silk texture were emerged, which further result in the enhancement in surface area and pore structure. Thus, it can better encapsulate and protect the nanoparticles …”
Section: Resultsmentioning
confidence: 99%